Influence of internet usage on social and subjective well-being of Sri Lankan GLIS - Wickramasinghe, C. Nalaka; Ahmad, Nobaya (The Journal of Happiness and Well-Being & Kiperonline Academic, 2013)
The Internet has significantly contributed to the drastic growth of technological inventions and innovation in the world. The majority of the inventors in developing countries is independent inventors work on inventions by their own interest. The Internet has been one of the leading knowledge repositories for these independent inventors to search clues for their inventions. Owing to the self-driven behavior of the independent inventors, they might gain success and perceive happiness through the inventive activities that involved searching and creation of new knowledge. However, there is hardly any study that explains the influence of the Internet usage on social and psychological aspects of grassroots level inventors (GLIS). Therefore, the existing knowledge on how the Internet usage influence on social capital, connectedness, success and subjective well-being of inventive community in developing countries is not exact. Present study explores the influence of the Internet usage on social capital, community connectedness, inventive achievements and subjective well-being of the grassroots level inventive community of Sri Lanka. Findings suggest that the Internet has significant direct influence on the subjective wellbeing of GLIS in Sri Lanka. Further The Internet usages indirectly influence the subjective well-being through social capital and connectedness. However, The Internet usage has not significantly influenced on the objective inventive achievements of the GLIS in Sri Lanka.